2018
DOI: 10.24880/maeuvfd.495969
|View full text |Cite
|
Sign up to set email alerts
|

Morphological aspects of the pancreas in the rat and the rabbit: an investigation into the location, ducts, arteries and veins

Abstract: The aim of the present study was to determine both the location of the pancreatic duct and the anatomical variation in the pancreatic ducts of rat and rabbit. Following administration of ether anesthesia, the abdomens were opened. Catheters were placed in the ileocolic vein, junction of the duodenum and jejunum, and into the aorta. All arteries, veins and pancreatic ducts were filled with red, blue and white dyed latex, respectively. The rat pancreas was consisted of three lobes, while the rabbit pancreas was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The anatomical structure of the chinchilla pancreas is comparable to what has been described for the rabbit (7), in which the same division into three lobes has been observed. The human pancreas is a compact organ that is protected from severe trauma by being located close to the back wall of the abdominal cavity.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The anatomical structure of the chinchilla pancreas is comparable to what has been described for the rabbit (7), in which the same division into three lobes has been observed. The human pancreas is a compact organ that is protected from severe trauma by being located close to the back wall of the abdominal cavity.…”
Section: Resultssupporting
confidence: 83%
“…Previous investigations have looked at the anatomy of pancreatic ducts and the location of their outlet in relation to duodenal papillae. In the rat, several pancreatic ducts open to the common bile duct at various points, but before entering the duodenum at the duodenal papilla (7,10). The minor duodenal papilla is absent in rats, so the distal segment of the common bile duct contains a mixture of liver and pancreatic secretions (33).…”
Section: Resultsmentioning
confidence: 99%
“…Harvesting of the pancreas: Access to the pancreas was achieved by opening the rabbit's abdominal cavity, where the pancreas, distinguished by its crescent-shaped, dark red appearance, was separated from the spleen and the duodenal region. The harvested pancreas, characterized by its pink color and dispersed irregular glands, was xed in a 4% paraformaldehyde solution for subsequent analysis (Haligur et al, 2018;Toledo-Pereyra, 1988). Euthanasia: After anesthesia, the rabbits were humanely euthanized by intracardiac injection of air to ensure swift and painless death.…”
Section: 5tissue Harvesting and Subsequent Processingmentioning
confidence: 99%
“…Rsv has been studied for a several decades in different therapeutic research areas and epidemiological studies have observed the relationship between consumption of Rsv and healthy (16,17). Laboratory animals are used in many experimental studies (18)(19)(20)(21). In numerous experimental studies reported that resveratrol possesses many bioactivities and has beneficial for healthy like antioxidant, anti-inflammatory, improving diseases and also has a hepatoprotective effect (22,23).…”
Section: Introductionmentioning
confidence: 99%